The future of food in India: A 2050 perspective - Balaji, Sedithippa Janarthanan; Birthal, Pratap S.; Pal, Barun Deb; Thurlow, James; Gotor, Elisabetta; Sharma, Purushottam; Srivastava, S. K.; Kingsly, Immanuelraj T.; Naresha, N. (Indian Council of Agricultural Research, 2025)
India’s agri-food system is poised for a significant transformation driven by its potential for rapid economic growth and increasing globalization. As these forces reshape consumer preferences, there is a growing demand for nutrition-rich foods. This shift presents a unique opportunity for India to reimagine its agri-food system over the next quarter-century, aligning it with evolving consumer needs while addressing persistent nutritional challenges.